(untitled) (Reflection and Critique Law Magazine, 2022)
The purpose of this article is to analyze the possibility of applying systemic law to all collective rights. For that, starting from the hypothetical-deductive method, and using as methodology the bibliographic research consisting of books, scientific articles, legislation and jurisprudence, we sought to investigate the various possibilities of collective conflict resolution, such as judicial collective actions, restorative justice , multiport court and family systemic constellation and its relationship with systemic law. In the end, it was possible to conclude by the feasibility of using systemic law in the treatment of the most varied conflicts of a collective nature.